2017
DOI: 10.1111/exd.13418
|View full text |Cite
|
Sign up to set email alerts
|

Regression of diffuse B‐cell lymphoma of the leg with intralesional gentian violet

Abstract: In this case report, a patient of primary cutaneous diffuse B-cell lymphoma, leg type was treated with intralesional gentian violet as she was judged to be too medically fragile for conventional chemotherapy due to advanced age and multiple serious comorbidities. Gentian violet (crystal violet/hexamethyl pararosaniline) is a triphenylmethane dye. It has been shown to have an inhibitory effect on NADPH oxidase, an enzyme family which is found in abundance in reactive oxygen-driven tumors such as melanoma and ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…13 Our laboratory discovered that it is an NADPH oxidase inhibitor and, as such, found that it has antitumor properties in patients with melanoma and lymphoma in vivo. [14][15][16][17] Based on our work, gentian violet was found to have efficacy against early plaque-stated CTCL. In this case report, we demonstrate remission of advanced CTCL using a regimen containing gentian violet, radiation, and mogamulizumab.…”
Section: Discussionmentioning
confidence: 73%
“…13 Our laboratory discovered that it is an NADPH oxidase inhibitor and, as such, found that it has antitumor properties in patients with melanoma and lymphoma in vivo. [14][15][16][17] Based on our work, gentian violet was found to have efficacy against early plaque-stated CTCL. In this case report, we demonstrate remission of advanced CTCL using a regimen containing gentian violet, radiation, and mogamulizumab.…”
Section: Discussionmentioning
confidence: 73%
“…The mechanism of this antitumor activity is not fully understood, although GV has been shown to inhibit nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, which decreases local reactive oxygen species and contributes to antiangiogenesis and might inhibit certain tumor suppressor pathways 3, 4. Regression of primary cutaneous diffuse B-cell lymphoma after injection of intralesional GV has been reported, 5 and abrogation of NADPH oxidase–mediated tumor promotion in addition to facilitating antitumor activity have been proposed as mechanisms by these investigators. GV also inhibits NF-kB, also possibly through NADPH oxidase inhibition, which has been implicated in proliferation of CTCL tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role as an antifungal and antibacterial agent, GV has anticancer properties. [25][26][27][28][29][30] Prior work 27, [31][32][33] has found that GV inhibits nicotimamide adenine dinucleotide phosphate oxidases, NF-κB, and ANG-2 while inducing p53 and IκB in various cell types. Our current findings add to this knowledge base by detailing the association between GV and CTCL cells.…”
Section: Discussionmentioning
confidence: 99%